Two degrees - Gratz, Alan, 1972- (2022)
When three children endure separate climate change disasters--a wildfire in the California woods, a close encounter with a hungry polar bear in Canada, and a massive hurricane in Florid--they emerge from their experiences committed to changing the world.
Ages 8-12.
Grades 4-6.
Keywords: Global warming -- Juvenile fiction; Climatic changes -- Juvenile fiction; Survival -- Juvenile fiction; Adventure stories; Global warming -- Fiction; Climatic changes -- Fiction; Survival -- Fiction; Adventure and adventurers -- Fiction; JUVENILE FICTION / Science & Nature / Weather; JUVENILE FICTION / Action & Adventure / Survival Stories; Action and adventure fiction